Publishers, Readers, and Digital Engagement - Martens, Marianne; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book demonstrates how the roles of "author," "marketer," and "reviewer" are being redefined, as online environments enable new means for young adults to participate in the books they love. Prior to the expansion of digital technologies around reading, teachers, parents and librarians were the primary gatekeepers responsible for getting books into the hands of young people. Now publishers can create disintermediated digital enclosures in which they can communicate directly with their reading audience. This book exposes how teens contribute their immaterial and affective labor as they engage in participatory reading experiences via publishers' and authors' interactive websites and use of social media, and how in turn publishers are able to use such labor as they get invaluable market research, peer-to-peer recommendations, and even content which can be used in other projects all virtually free-of-charge.
Acknowledgements -- Preface -- Introduction -- 1. A Brief History of the Field -- 2. Branding Books, Branding Readers: Marketing to Teens in the Digital Age -- 3. From Random Buzzers to Figment: Teens' Affective and Immaterial Labor -- 4. Twilight Saga.com (2009-2012) - Fandom and the Lifespan of a Corporate Fan Site -- 5. Reading The Amanda Project - a Lifecycle of a Pioneering Multiplatform Book (2009-2012) -- 6. Conclusion -- Methodological Appendix -- Notes -- Bibliography -- Index.-.
Keywords: Books-History.; Technology in literature